Intergenerational Effect of Maternal Childhood Maltreatment on Next Generation’s Vulnerability to Psychopathology: A Systematic Review With Meta-Analysis - Su, Yingying; D’Arcy, Carl; Meng, Xiangfei (Trauma, violence & abuse, 2022)
Many studies have identified the multiple negative consequences of childhood maltreatment on subsequent mental health. However, research on the intergenerational effect of maternal childhood maltreatment has not been systematically synthesized. This meta-analysis aimed to provide a quantitative estimate of the intergenerational effect of maternal childhood maltreatment on their offspring’s psychopathology. Electronic databases and gray literature were searched for English-language prospective cohort studies. Two reviewers independently extracted data and assessed study quality with the Newcastle-Ottawa Scale. This review only included those studies with (1) maternal childhood maltreatment occurring prior to 18 years of age, (2) using a clear and reliable assessment for maltreatment exposure and offspring’s mental health problems prior to age 18. Random-effect models were used to calculate the pooled effect size of maternal childhood maltreatment on offspring’s psychopathology, and meta-regression was used to explore potential confounders. Twelve studies met eligibility criteria. Significant heterogeneity was found across selected studies. Maternal childhood maltreatment was found to have a small but significant effect on the offspring’s depression and internalizing behaviors (r = .14, 95% confidence interval [.09, .19]). Two moderators were found, maternal depression and ethnicity. Maternal depression reduced the effect size of maternal maltreatment on offspring’s depression and internalizing disorders. The offspring of non-Caucasian mothers who had a history of childhood maltreatment faced a higher risk of mental health problems. There was no evidence of publication bias. This review provides robust evidence to reinforce the need for policies to reduce its occurrence, as it can influence not just one but two or possibly more generations.